ANALISIS PENGEMBANGAN KURIKULUM BAHASA ARAB : MIN 01 BANDA ACEH - chairani, Ully shifa (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2024)
Curriculum can be interpreted as a collection of learning plans consisting of well-organized, planned and structured teaching materials that are connected to various activities and social relationships in the educational area. The objectives of this research are to know the vision, mission and objectives at MIN 01 Banda Aceh, to know the implementation of MIN 01 Banda Aceh learning, and to know the evaluation of MIN 01 Banda Aceh learning. In this research, researchers used the library research method. Where researchers apply data collection techniques while analyzing sources from books, journals, articles, seminar results and interviews. The result is that the curriculum used at MIN 10 Banda Aceh is generally in accordance with the 2013 curriculum, because in general it focuses on character and competency-based learning which requires children to be active in learning as stated in the meaning and objectives of the 2013 Curriculum.